Sensitivity and Specificity of 2 Autism Screeners Among Referred Children Between 16 and 48 Months of Age. Issue 3 (April 2018) - Salisbury, Louisa A.; Nyce, Jonathan D.; Hannum, Charles D.; Sheldrick, R. Christopher; Perrin, Ellen C.
ABSTRACT: Objective: Autism screening is recommended by the American Academy of Pediatrics and the Centers for Disease Control and Prevention at ages 18 and 24 months. Popular screening tests have been validated for the age range of 16 to 30 months. However, only a minority of children with autism spectrum disorder (ASD) are identified by age 3 years, and many are not identified until after they enter school. Thus, we aimed to measure the sensitivity and specificity of 2 available screening tests for ASDs in children older than 30 months. Methods: We assessed the sensitivity and specificity of 2 ASD screening tools administered to parents of children who were referred to a developmental clinic between the ages of 16 and 48 months: the Modified Checklist for Autism in Toddlers (M-CHAT) and the Parent's Observations of Social Interactions (POSI), which is a component of a comprehensive screening instrument called, the Survey of Well-being of Young Children. Results: Both the M-CHAT and the POSI had acceptable sensitivity (≥75%) among children across the age range studied. Their specificity was limited by the fact that the study was conducted in a developmental referral clinic. Conclusion: Two readily available screening tools, the POSI and the M-CHAT, have acceptable sensitivity in evaluating risk for autism in children at least to age 48 months. Further research should investigate their sensitivity and specificity when used in primary care settings.